Determination of Health Literacy Level in Individuals with Osteoporosis - Fatih Okan; Sevil Okan (Galenos Yayinevi, 2023)
Objective:The study aimed to determine the health literacy level of individuals diagnosed with osteoporosis.Materials and Methods:A descriptive cross-sectional study was conducted with 156 individuals diagnosed with osteoporosis between April 2021 and April 2022. Data were collected using the personal information form and the Turkish Health Literacy Scale-32.Results:It was determined that 48.1% (n=75) of the individuals included in the study had an inadequate, 23.1% (n=36) problematic-limited, 17.3% (n=27) adequate, 11.5% (n=18) excellent level of health literacy. It was found that the total mean score of health literacy was higher in individuals aged 65 and over compared with those under 65 years of age; individuals with university degrees, compared to primary, secondary, and high school graduates; individuals living in an extended family compared to those living in a nuclear family; individuals living in the city center, compared to those living in the district center and village/town; individuals whose income is equal to their expenses and income is more than their expenses than those whose income is less than their expenses (p<0.05).Conclusion:Approximately two-thirds of individuals diagnosed with osteoporosis have limited or insufficient level of health literacy. Health professionals should evaluate the health literacy level of individuals with osteoporosis, and as a result, they should plan appropriate information methods and training programs for the patient.